Injuries associated with law enforcement use of force. (April 2013) - Adedipe, Adeyinka; Maher, Patrick J; Strote, Jared
Prehospital personnel and physicians working in acute care settings need to be cognizant of the issues related to law enforcement use of force in order to properly evaluate and manage these patients. Types of force used by law enforcement range along a spectrum from physical presence to lethal use of firearms. Although the vast majority of use of force incidents does not lead to significant injury, certain weapons and situations may require more extensive evaluation and higher levels of concern.